หน่วยสาธิตปั้มความร้อนชนิดพลังงานเคมี โดยใช้ระบบไอโซโพรพานอล/อะซีโตน/ไฮโดรเจน - อิทธิกร กลิ่นโซดา (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Chemical heat pump is another alternative to improve energy utilization by recovering waste heat or low-temperature heat by endothermic reaction, converting the heat into chemical energy and liberating as high-temperature heat by exothermic reaction. In this research, the isopropanol/acetone/hydrogen chemical heat pump process was set up to study the parametric effect on the performance of this process. The reversible reactions of an isopropanol/acetone/hydrogen chemical heat pump were studied by using Raney-Ni as a catalyst. The parameters such as reactant flowrate, temperature reaction and catalyst quantities were investigated. It was found that temperature, catalyst weight, isopropanol and nitrogen flow rates had affected on endothermic reaction conversion. The conversion of forward reaction was 9.05%. While the catalyst weight, hydrogen and acetone ratio and nitrogen flow rates were the important factors for the backward reaction, the conversion of acetone hydrogenation was 13.02%. For thermal efficiency, COP of this process were 0.38 and 1.79 respectively and exergy efficiency was 0.44